2019
DOI: 10.1016/j.jdent.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of genotypes, antimicrobial resistance and virulence profiles of oral and non oral Enterococcus faecalis from Brazil, Japan and the United Kingdom

Abstract: Objectives:To determine whether phenotypic and genotypic differences amongst isolates of Enterococcus faecalis relate to geographical and clinical origin. Methods: E. faecalis from primary endodontic infections in Brazilian patients (n=20), oral infections in UK patients (n=10), and non-oral infections in Japanese patients (n=9) were studied. In addition, 20 environmental vancomycin resistant Enterococcus faecalis (VRE) isolates from a UK hospital were analysed. For all isolates, polymerase chain reaction (PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Wang et al (2011) demonstrated that the prevalence of E. faecalis in the root canal system had been correlated with its occurrence in saliva. Meanwhile, some authors suggested nosocomial transmission from environmental surfaces in dental surgeries due to the robust nature of the microorganisms (Vidana et al 2011;Lins et al 2019), while others proposed foodborne transmission (Zehnder and Guggenheim 2009). However, Vidana et al (2011) examined the genetic relationship between E. faecalis from root canals and isolates from different host sources and found that isolates from the root canals were not related to those from the typical gastrointestinal microflora, and none of these patients was recorded to have enterococci in their saliva.…”
Section: Enterococcus Faecalismentioning
confidence: 99%
“…Wang et al (2011) demonstrated that the prevalence of E. faecalis in the root canal system had been correlated with its occurrence in saliva. Meanwhile, some authors suggested nosocomial transmission from environmental surfaces in dental surgeries due to the robust nature of the microorganisms (Vidana et al 2011;Lins et al 2019), while others proposed foodborne transmission (Zehnder and Guggenheim 2009). However, Vidana et al (2011) examined the genetic relationship between E. faecalis from root canals and isolates from different host sources and found that isolates from the root canals were not related to those from the typical gastrointestinal microflora, and none of these patients was recorded to have enterococci in their saliva.…”
Section: Enterococcus Faecalismentioning
confidence: 99%
“…32 With regard to the evaluation of the antimicrobial action of endodontic agents, a strain of Enterococcus faecalis previously isolated from endodontic infection was used, identified by MALDI-TOF and PCR for 16S rRNA, and subjected to trypticase soy agar (TSA) having obtained the result of strain resistant to antibiotics. 33 Other authors reported a variation between 24 to 77% in the prevalence of Enterococcus faecalis in the root canals, and this bacterium could penetrate the dentinal tubules as well as the potential to be the infectious agent itself. 15,33,34 The formation of the biofilm for the study occurred for 21 days in human dentin blocks standardized in 5 mm in length, with similarity between the sample confirmed by the equivalence of the dentine volume weighing 0.2 g. Interestingly, this lifetime of 21 days, biofilm is more resistant to agents used in endodontic treatments.…”
Section: Discussionmentioning
confidence: 98%
“…33 Other authors reported a variation between 24 to 77% in the prevalence of Enterococcus faecalis in the root canals, and this bacterium could penetrate the dentinal tubules as well as the potential to be the infectious agent itself. 15,33,34 The formation of the biofilm for the study occurred for 21 days in human dentin blocks standardized in 5 mm in length, with similarity between the sample confirmed by the equivalence of the dentine volume weighing 0.2 g. Interestingly, this lifetime of 21 days, biofilm is more resistant to agents used in endodontic treatments. 35 Arias-Moliz et al 36 found a minimal biofilm eradication of Enterococcus faecalis after exposure of 1, 5 and 10 minutes in different concentrations of NaOCl and CHX; the findings were that NaOCl was capable of minimal eradication of the biofilm after a period of one minute in concentrations below 0.1%, while CHX achieved this result after five minutes at 0.2%36.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It not only links epithelial cells to virulent characteristics and resistant determinants via plasmid exchange and colonization but also attaches to the network of extracellular proteins (Wagner et al, 2018). Different studies have provided evidence that E. faecalis harbors the agg gene most (Guzman Prieto et al, 2016;Lins et al, 2019;Farman et al, 2019).…”
Section: Virulence Genes/factorsmentioning
confidence: 99%